Perinatal outcome and social background of social high-risk pregnant women in our hospital - Obata, Shintaro; Sanada, Michio; Yamanouchi, Miki; Hanawa, Shinsuke; Sato, Shiro; Unno, Yoichi; Nishikata, Noriko (Journal of Japan Society of Perinatal and Neonatal Medicine, 2024)
We investigated the perinatal outcome and social background of social high-risk pregnant women（SHW）who received treatment at our hospital. Among 3,193 deliveries that occurred at our hospital between 2017 and 2022, we included 602 speciﬁc pregnant women and 2,591 general pregnant women（GPW）. We evaluated social risk factors and perinatal outcome. The factors we considered included multiple factors（41.5%）, mental illness（22.3%）, foreign nationality（17.1%）, unmarried status（7.1%）, economic deprivation（2.5%）, lack of support（1.8%）, being widowed or not yet receiving medical care（2.0%）, being young（aged below 20）（1.7%）, livelihood protection（1%）, adoption（0.3%）, intellectual disability（0.2%）, Domestic Violence（0.2%）, and giving birth without visiting antenatal clinics（0.2%）. Perinatal outcome were not signiﬁcantly diﬀerent between the number of cases with umbilical Artery pH < 7.1 and Apgar score. The perinatal outcomes of SHW are comparable to those of GPW. However, addressing the needs of SHW necessitated multidisciplinary collaboration.